Is the Development of Gestational Diabetes Associated With the ABO Blood Group/Rhesus Phenotype? - Lemaitre, M.; Passet, M.; Ghesquière, L.; Martin, C.; Drumez, E.; Subtil, D.; Vambergue, A. (Frontiers in Endocrinology, 2022)
Aims There are few published data on the putative association between the ABO blood group/rhesus (Rh) factor and the risk of developing gestational diabetes mellitus (GDM). Methods: All women having given birth at Lille University Medical Center (Lille, France) between August 1st, 2017, and February 28th, 2018, were tested for GDM, using the method recommended in the French national guidelines. The risk of GDM was assessed for each ABO blood group, each Rh phenotype and combinations thereof, using logistic regression models. Results: 1194 women had at least one GDM risk factor. The percentage of GDM varied with the ABO group (p=0.013). Relative to group O women, group AB women were more likely to develop GDM (OR = 2.50, 95% CI [1.43 to 4.36], p=0.001). Compared with the Rh-positive O group, only the Rh-positive AB group had an elevated risk of developing GDM (OR = 3.02, 95% CI = 1.69 to 5.39, p < 0.001). Conclusions: Our results showed that Rh-positive group AB women have a greater risk of GDM. With a view to preventing GDM, at-risk individuals could be identified by considering the ABO blood group phenotype either as a single risk factor or in combination with other risk factors.